The interplay of Kappa and core populations in the solar wind: Electromagnetic electron cyclotron instability. Issue 12 (18th December 2014) - Lazar, M.; Poedts, S.; Schlickeiser, R.
Abstract: Recently, a realistic parameterization was proposed for the kinetic anisotropy and the resulting instabilities in the solar wind plasma. This parameterization is based on observations of the particle velocity distribution, which always comprises a Maxwellian population at low energies, viz. the core, and a suprathermal halo in the tail of the distribution which is best described by the Kappa (power law) models. The cyclotron instability, driven by an anisotropic electron halo, was found to be inhibited by the finite thermal spread in the core, and this effect is highly dependent on the halo‐core relative density. In this paper, the interplay between the Kappa and Maxwellian populations is further investigated for more complex (less idealized) situations when both the core and halo temperatures are anisotropic. Growth of this instability is markedly stimulated by the core anisotropy. The wave numbers that are stable for an isotropic core become unstable even for small anisotropies of this population. Just a modest increase of the core anisotropy from A c = T ⊥ / T ∥ =1.2 to 2 causes the growth rates to enhance by 1 order of magnitude, and the range of unstable wave numbers to extend considerably. When the anisotropies in the core and halo are comparable, the growth rate exhibits two distinct peaks, the first driven by the halo at lower wave numbers and the second driven by the core. However, the first peak is inhibited by the suprathermal populations, while the second peak is sustained, suggesting a more intricate connection between the core and Kappa populations. Key Points: Kappa models facilitate realistic predictions in space plasma The first formalism assuming both the core and halo temperatures are anisotropic The interplay of the Kappa and core populations unveiled in the EMEC instability